Development of a DNA computing model for Boolean Circuit - Boruah, Kuntala; Dutta, Jiten Ch (2016 2nd International Conference on Advances in Electrical, Electronics, Information, Communication and Bio-Informatics (AEEICB), 2016)
In this paper, we present a DNA based algorithm to simulate the logic functionality of any Boolean Circuit. The inherent hybridization property of Deoxyribonucleic acid (DNA) is the key operation used throughout the model. The contribution of this paper is to introduce an algorithm involving a relatively less number of biochemical reactions. The proposed theoretical model is reusable and has a wide range of applicability in simulating Boolean functionality corresponding to any truth table.